The Effectiveness of Instagram Marketing on Improving Profit and Activity for Small Businesses - Cabuang, Sophia Alexandra D. (Animo Repository, 2022)
Social media platforms have become headway for businesses to create an online presence and allow communications between buyer and seller in the online world. Accordingly, the role of using Instagram as a marketing strategy for businesses is proven effective, however its impact to businesses' venture performance in comparison to traditional marketing calls for extensive assessment. Selected business owners who utilizes Instagram in propagating their businesses were interviewed to establish a correlation between business' operations to the business' development. The interviews gave insights on how Instagram's features allowed the respondents to reach their audience, focus on showing their products or services to interested individuals, and garner more order requests. Consequently, factors such as target audience, and use of social media heavily influence the strategic planning of business owners. To conclude, all respondents reacted positively to recommending Instagram to other business owners, hence it can be inferred that Instagram is an effective platform to market products, a great value to small businesses with limited budgets.